Data and Metadata Exchange Design with SDMX Format using Web Service for Interoperability Statistical Data - Jaka Sembiring; Ana Uluwiyah (Institute of Advanced Engineering and Science, 2015)
Today’s concept of Open Government Data (OGD) for openness, transparency and ease of access of data owned by government agencies becomes increasingly important. This initiative emerges from the demand of data users for the data belongs to the government agencies. The data services providing an easy access, cheap, fast, and interoperability are needed by the users and becomes important indicator performance for respective government agencies. Statistical Data and Metadata Exchange (SDMX) is a new standard format in the data dissemination activities particularly in the exchange of statistical data and metadata via Internet. In this respect SDMX support the implementation of OGD project. This paper is on the technical design, development and implementation of data and metadata exchange service of statistical data using SDMX format to support interoperability data through web services. Three results are proposed: (i) framework for standardization of structure of statistical publications data model with SDMX; (ii) design architecture of data sharing model; and (iii) web service implementation of data and metadata exchange service using Service Oriented Analysis and Design (SOAD) method. Implementation at Statistics Indonesia (BPS) is chosen as a case study to prove the design concept. It is shown through quantitative assessment and black box testing that the design achieves its objective. DOI: http://dx.doi.org/10.11591/telkomnika.v14i2.7505